Chromatic Adaptation in Marine Synechococcus Strains - Palenik, Brian (American Society for Microbiology, 2001)
Characterization of two genetically distinct groups of marine Synechococcus sp. strains shows that one, but not the other, increases its phycourobilin/phycoerythrobilin chromophore ratio when growing in blue light. This ability of at least some marine Synechococcus strains to chromatically adapt may help explain their greater abundance in particular ocean environments than cyanobacteria of the genus Prochlorococcus.